Treatment Parameters of Photobiomodulation in the Prevention of Non-surgical Cancer TreatmentInduced Oral Mucositis: A Review of Preclinical Studies: Photobiomodulation in the Prevention of Chemotherapy-Induced Oral Mucositis - Agbele, Alaba Tolulope; Hejazi, Sedigheh Marjaneh; Dehpour, Ahmad Reza; Jafari , Razieh Mohammad; Elyassi , Arash; Bagheri, Mahmoud; Seydi , Mojtaba (Journal of Lasers in Medical Sciences, 2021)
Introduction: The most important side effect after non-surgery cancer treatment (NSCT) is oral mucositis (OM) which degrades the quality of life. Using photobiomodulation (PBM), formerly known as low-level laser therapy (LLLT), in the prevention of NSCT-induced OM was widely studied. Hence, this review evaluates the efficacy of optical treatment parameters behind the working process of PBM in preventing NSCT-induced OM in preclinical studies. Methods: Using the PubMed, Scopus, and Embase databases, the present study systematically reviewed existing preclinical studies for optical treatment parameters of PBM in preventing NSCTinduced OM in experimental models without restriction on the year of publication. Results: In total, 51 articles were recognized during the search of the literature, and only 16 research papers were included in this review, taking into consideration the inclusion as well as exclusion benchmarks. The reviewed studies showed that a consensus has yet to be reached on the optimal PBM treatment parameters in preventing NSCT-induced OM. However, a wavelength of 660 nm, a power density of 40 mW as well as fluence which ranged between 2 and 6 J/cm2 were mostly utilized in the included studies. Furthermore, the severity of NSCT-induced OM was reduced following PBM application with no reported severe side effects. Conclusion: The efficacy of PBM with the associated optical parameters is a promising strategy in preventing NSCT-induced OM. However, the optimal parameters of PBM need to be investigated. DOI: doi:10.34172/jlms.2021.54